Mobile communication and the protection of children - Ong, Rebecca, 1961- (Meijersreeks, 2010)
Mobile phones and other smart connected devices have fundamentally changed contemporary life. Globally, we see an unprecedented explosion of new generation mobile phones. More precisely, mobile communication is nowadays really pervasive in social life. For instance, children and young persons are emerging as active players in the wonderful world of ringing and being ringed. Many of them are attracted by intriguing ring tones. However, the rapid mobile diffusion among children and young people raises a number of crucial questions -- $c Source other than Library of Congress.